A Model for Librarians to Assess the Digital Capability of Research Teams. Issue 1 (2nd January 2020) - Wolski, Malcolm; Krahe, Michelle; Richardson, Joanna
ABSTRACT: This paper examines the issue of digital capability at the research team level, specifically their ability to adapt to an uncertain digital future. Within higher education, there is a driving imperative to adapt to the new digital environment not only in areas involved in learning and teaching but also among research teams. While libraries play an important role in developing the digital literacy of researchers as individuals, little attention has been paid to the digital capability of the research team. A review of the literature was undertaken of digital transformation frameworks and models across business, government and higher education. No applicable models or frameworks were found to be suitable for a research team environment. A digital capability model was developed, drawing upon the critical elements discussed in the literature. This model enables library staff to assess the digital capability of the research team, allowing them to not only tailor their services to specific research teams but also driving changes to overall service offerings to better meet the needs of researchers across the organisation. Using this model changes the nature of library staff's conversation with research team leaders.